A constitutional theory of the family - Alessandro Cigno (Institute for the Study of Labor (IZA), 2005)
The paper re-examines the idea that a family can be viewed as a community governed by a self-enforcing constitution, and extends existing results in two directions. First, it identifies circumstances in which a constitution is renegotiation-proof. Second, it introduces parental altruism. The behavioural and policy implications are illustrated by showing the effects of public pensions and credit rationing. These implications are not much affected by whether altruism is assumed or not, but contrast sharply with the predictions of more conventional models.
Keywords: C72; D02; D13; D71; D74; D91; H55; J13; J14; 330; families; self-enforcing constitutions; renegotiation-proofness; altruism; fertility; saving; transfers; attention; pensions; credit rationing; Familie; Familienökonomik; Altruismus; Fruchtbarkeit; Sparen; Alterssicherung; Kreditrationierung; Theorie